PENDAMPINGAN TERHADAP PEREMPUAN PEKERJA KORBAN KEKERASAN DALAM RUMAH TANGGA DI KABUPATEN BANYUMAS - Mariyawati, Mariyawati; Wulan, Tyas Retno; Muslihudin, Muslihudin; Wuryaningsih, Tri; Sutoyo, Ignatius Suksmadi (Jurnal Analisa Sosiologi, 2023)
Domestic violence is a manifestation of gender inequality in a patriarchal culture. The phenomenon of working women is the progress and success of women in opposing patriarchal culture. The UPTD PPA of Banyumas Regency is a government agency authorized to handle cases of gender- and child-based violence under the auspices of the DPPKBP3A service and the KPPPA RI umbrella. This study aims to identify the processes and roles of the government in intervening in cases of domestic violence, as well as the obstacles that occur during the mentoring process for working women who are victims of domestic violence. This study uses a qualitative research method with a phenomenological approach. The data collection process was carried out through in-depth interviews, observation, and documentation. The results of the study show that the mentoring process at the UPTD PPA Banyumas Regency has been adjusted to the standard of Dexterous services stipulated in the Minister of KPPPA RI Number 2 of 2022 by implementing psychosocial-based assistance. This issue is because the socio-cultural conditions of the Banyumas society consider domestic violence as a disgrace even though it has caused psychological, sexual, and physical violence. The ability of women to work in the public sector makes women experience a double burden. A patriarchal culture places women in a subordinate position while men are superior and cause both of them to fail in carrying out their roles as husband and wife, which manifests itself in the form of violence. The obstacles faced are the lack of human resources, facilities, and infrastructure that do not yet support the needs of persons with disabilities and the elderly. The presence of the UPTD PPA is a form of state presence and power in intervening in cases of domestic violence. Keywords: Domestic Violence, Patriarchal Culture, WomenAbstrakKekerasan dalam rumah tangga merupakan manifestasi dari ketidakadilan gender di tengah budaya patriarki. Fenomena perempuan pekerja merupakan sebuah kemajuan dan keberhasilan perempuan dalam menentang budaya patriarki. UPTD PPA Kabupaten Banyumas merupakan lembaga pemerintah yang berwenang menangani kasus kekerasan berbasis gender dan anak di bawah naungan dinas DPPKBP3A dan payung KPPPA RI. Penelitian ini bertujuan untuk mengidentifikasikan proses dan peran pemerintah dalam mengintervensi kasus KDRT, serta kendala yang terjadi saat proses pendampingan bagi perempuan bekerja korban KDRT. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Adapun proses pengambilan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukan bahwa proses pendampingan di UPTD PPA Kabupaten Banyumas telah disesuaikan dengan standar layanan Cekatan yang diatur dalam Permen KPPPA RI Nomor 2 Tahun 2022 dengan menerapkan pendampingan berbasis psikososial.  Hal ini karena kondisi sosial budaya masyarakat Banyumas  menganggap KDRT sebagai aib meskipun sudah mencapai kekerasan psikis, seksual, dan fisik. Kemampuan perempuan bekerja di sektor publik justru menjadikan perempuan mengalami beban ganda. Budaya patriarki yang masih menempatkan perempuan pada posisi subordinat sedangkan laki-laki sebagai superior dan menyebabkan keduanya gagal dalam menjalankan peran sebagai suami isteri, hingga termanifestasikan dalam bentuk kekerasan. Kendala  yang dihadapi yaitu kurangnya sumber daya manusia, sarana dan prasarana belum mendukung kebutuhan penyandang disabilitas dan lansia. Kehadiran UPTD PPA merupakan bentuk kehadiran dan kuasa negara dalam mengintervensi kasus KDRT.Kata Kunci : Kekerasan Domestik, Budaya Patriarki, Perempuan